The Curriculum Structure of Pesantren in Madura: Uncovering the Values of Religious Moderation - Hadi, Nurul; M. Hasbullah; Abd. Rahman Romadhon; Khomisatul Fajriyah; Karomatun Nafisah; Ahmad Sudi (State Islamic Institute of Madura, 2025)
This research aims to analyze the curriculum structure of Islamic boarding schools (Pesantren) in Madura and to determine the extent to which the values of religious moderation are reflected in the curriculum. This research uses a qualitative approach with a descriptive research type. The research results show that the curriculum structure of Pesantren in Madura generally still refers to classical Islamic texts (kitab kuning) based on the Shafi'i school of thought. The curriculum encompasses a range of Islamic knowledge disciplines such as Fiqh, Ushulfiqh, Hadith, Tafsir, and others. The values of religious moderation are reflected in the content of the Pesantren curriculum, such as the emphasis on understanding moderate (wasathi) Islam, the teaching of the concepts of tolerance, and the appreciation of pluralism. In addition, activities in Pesantren also reflect the values of moderation, such as interfaith and cross-cultural dialogues and cultural performances. The books taught in Pesantren, especially the works of moderate Sunni scholars, contain teachings that support religious moderation, such as the importance of cultivating tolerance, respecting diversity, and avoiding extremism. This study concludes that the curriculum structure of Pesantren in Madura reflects values of religious moderation, although further development and reinforcement are still needed. Such efforts are essential to maintaining the role of Pesantren as an educational institution that cultivates a generation of moderate and tolerant Muslims.